Human Phylogeny in the Light of East African Findings - Hałaczek, Bernard (Anthropological Review, 1977)
On the basis of recent (collected up to the end of 1975) data on fossil hominids, some traditionally held statements pertaining to anthropogenesis may be open to doubt. These statements are: 1. Phylogenetic relation of the genus Australopithecus to the genus Homo, 2. Origin of the genus Homo from the Middle Pleistocene, 3. Radiative evolution of Hominidae starting from a single species.In the article, a review of the most recent discoveries done in Africa (Kenya — Turkana Lake, formerly Lake Rudolf; Ethiopia — Omo valley and Hadar region; Tanzania — Laetolil) is provided. Particular attention was paid by the author to the dating of finds. In the concluding section of the paper, a new, modified shape of the phylogenetic tree of the hominid family is proposed.